“Pretending to Be Cikgu”: Role Reversal Pedagogy in Peer-Led Arabic Vocabulary Learning in Malaysia - Masnun Masnun; Ahmad Durrun Nafis; Syaza Auni Irdyna (Universitas Islam Negeri Palangka Raya Raya, 2026)
Conventional Arabic vocabulary instruction in many Islamic secondary schools remains predominantly teacher-centered, relying heavily on memorization and teacher-led repetition, which often results in limited learner engagement, weak active retrieval, and low long-term vocabulary retention particularly in verb-based forms with complex morphological patterns. Responding to these pedagogical limitations, this study investigates the impact of role reversal pedagogy implemented through peer-led choral recitation in Arabic vocabulary learning within a Malaysian educational context. The instructional practice, locally conceptualized as “Pretending to Be Cikgu,” assigns selected students to temporarily assume the role of teacher by leading their peers in collective recitation of verb-based vocabulary drawn from Kitab Af‘āl al-Yawmiyyah. Employing a qualitative classroom-based research design, data were collected through classroom observations, student reflections, and teacher field notes. The findings reveal that peer-led choral recitation enhances learner engagement, collective participation, and vocabulary internalization. Students acting as instructional leaders demonstrated higher levels of responsibility, confidence, and active retrieval, while peers benefited from structured repetition and reduced speaking anxiety. The approach functioned as both a cognitive and social scaffold, reinforcing memory consolidation of morphologically inflected Arabic verbs and fostering a collaborative learning environment. The study concludes that role reversal pedagogy offers a learner-centered instructional model that addresses key shortcomings of conventional vocabulary instruction by shifting responsibility from teacher to students, promoting deeper lexical internalization and socially distributed learner autonomy in Arabic vocabulary learning.